Pengaruh Wadah Semai Berbahan Dasar Organik dan Fungi Mikoriza Arbuskula (FMA) Terhadap Pertumbuhan Semai Balsa (Ochroma bicolor Rowlee) - Sri Wilarso Budi; Rahmawati Rahmawati (Jurnal Silvikultur Tropika, 2020)
Balsa (Ochroma bicolor Rowlee) are generally sown using a polybag. Polybag made from plastic that is not easily destroyed or degraded so that it can cause problems for the environment. As an alternative, polybag can be replaced by using organic pot. This research aims to analyze the effect of the treatment of raw materials of organic pot and inoculation Arbuscular Mycorrhizal Fungi (AMF) towards growth of balsa (O. bicolor). This study used Completely Randomized Design (CRD) with two factors. The results showed that treatment of organic pot composition and interaction of addition of AMF has significant effect of height of balsa. A single treatment of organic pot composition has significant effect of total dry weight and diameter increment of balsa. A single treatment by adding AMF has significant effectfor increment of diameter, total dry weight, and percentage of mycorrhiza colonizationat the root ofbalsa. Keyword: Arbuscular Mycorrhizal Fungi (AMF), Balsa (O. bicolor), organic pot